Measuring θ12 despite an uncertain reactor neutrino spectrum - Emilio Ciuffoli; Jarah Evslin; Marco Grassi; Xinmin Zhang (Nuclear Physics B, 2016)
The recently discovered 5–7 MeV excess in the reactor neutrino spectral structure, corresponding to a prompt energy of 4–6 MeV, highlights that the uncertainty in the reactor neutrino spectrum is far greater than some theoretical estimates. Medium baseline (about 50 km) reactor neutrino experiments will deliver by far the most precise ever measurements of θ12. However, the theoretical reactor neutrino spectra, as they were recalculated in 2011, do not reproduce this excess. As a result, if a medium baseline experiment attempted to determine sin2⁡(2θ12) using the theoretical spectrum, the result would have a systematic upward bias of 1%, much larger than the expected uncertainty. We show that by using recent measurements of the reactor neutrino spectrum the precision of a measurement of θ12 at a medium baseline reactor neutrino experiment can be improved appreciably. We estimate this precision as a function of the 9Li spallation background veto efficiency and dead time.